Gogi's gambit - Schrefer, Eliot, 1978- (Schrefer, Eliot, 1978- Lost rainforest, 2019)
Gogi, a shadowwalker monkey, blessed with ability to control fire, joins his other shadowwalker allies at the site of the previous battle where they learn of a new eclipse that could have profound effects on the creatures that reside in their magical rainforest home of Caldera. Still learning to control their powers, Gogi and his allies must overcome interspecies prejudice and stereotypes and obtain a powerful object that can harness the power of the eclipse and keep the Ant Queen and her minions at bay.